1990
DOI: 10.1109/27.45516
|View full text |Cite
|
Sign up to set email alerts
|

Feed optimization for the slotted line antenna for high-density plasma production

Abstract: Abstract-Investigations on the optimization of feed structures for exciting the slotted line antenna for high-density plasma production are presented. Each feed structure used (except the direct feed) excites a preferred component of the wave electric/magnetic field. It is seen that the efficacy of plasma production using the different feeds depends directly on the relative importance of the field components (which the feeds excite) for the slow wave mode of the antenna. The optimal feed is shown to be a dipol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
3
16
0
Order By: Relevance
“…For this purpose, the dominant field components of the slow-wave mode of this antenna were determined initially [5]. Subsequently, experiments were performed [6] where different feed structures (auxiliary antennae) were placed within the SLA for exciting different components of the microwave field preferentially. It was expected that when the excited field component corresponded to a dominant field component of the slow-wave mode of the SLA, the excitation of this mode and hence the ensuing plasma production process as well would be most efficient.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, the dominant field components of the slow-wave mode of this antenna were determined initially [5]. Subsequently, experiments were performed [6] where different feed structures (auxiliary antennae) were placed within the SLA for exciting different components of the microwave field preferentially. It was expected that when the excited field component corresponded to a dominant field component of the slow-wave mode of the SLA, the excitation of this mode and hence the ensuing plasma production process as well would be most efficient.…”
Section: Introductionmentioning
confidence: 99%
“…c, B 1 : externally applied DC magnetic field, m~ mass of electron) of an electron into microwave frequency (w, 1 ) in an externally applied DC magnetic field. The plasma density (n~c) that corresponds to microwave frequency of 2.45 GHz is 7.46 x 10 10 cm-3 • It is found experimentally that the plasma density saturates nearly at n,c and coupling of microwave into plasma does not help for density enhancement [14]. However, a high density plasma can be obtained at off-resonance (we, >> w, 1 ).…”
Section: Singly Charged Ion Sourcesmentioning
confidence: 90%
“…It can be shown that at reson?.nce the wave becomes an electrostatic wave for 6 * 0 [14,16]. Since the phase velocity of the wave is slowed down considerably near resonance (Vphfc < < 1), it is possible for the plasma electrons to interact with the wave when the condition V 11 cos 6 = VPh is obeyed (V 11 -axial velocity of the electrons).…”
Section: Singly Charged Ion Sourcesmentioning
confidence: 98%
“…[1][2][3] The ECR plasma is produced by matching the cyclotron frequency of an electron in an externally applied direct current ͑dc͒ magnetic field to the microwave frequency and for the ECR plasma heating applications, the microwave is coupled to the R wave ͑electron wave͒ using a special type of antenna. Geller has converted a magnetic mirror machine into an ion source for the production of multiply charged ion beams.…”
Section: Introductionmentioning
confidence: 99%